Improving Students’ Speaking Skills through Cooperative Learning in Vocational School Context - Ilmi, Annisa Nurul (CV Insan Kreasi Media, 2023)
Speaking is one of important language skills that should be mastered by vocational school students in order to be able to compete in 21st century. It is of the most frequently utilized and most challenging language abilities. The aim of the study is to improve students’ speaking skills through cooperative learning. It categorizes as action research study consisting of plan, implementation, observation, and reflection adapted from Kemmis, McTaggart, and Nixon. Thirty six students who were in the tenth grade of Public Vocational School 7 Yogyakarta majoring tourism participated in the study. They consisted of 33 females and 3 males. Two cycles and eleven meetings were applied during the research. The data were collected through observation, interview, questionnaire, and assessment. The findings shows that the students’ speaking skills improved during the teaching and learning process through some activities such as using classroom English; applying cooperative learning methods: two stray two stay, think-pair-share, numbered heads together, and inside outside circle methods; encouraging the students to be aware with their performance and be able to do self-correction as well as giving feedback to other performance; adapting the learning materials to suit students’ needs; and motivating students to bring a dictionary and install electronic dictionary in their mobile. The students speaking scores before and after implementing cooperative learning show significant improvement from the total mean of the class 482.5 to 512.5. To sum up, cooperative learning is successful in improving the students’ speaking skills. The results of the research provide useful insight for teachers considering improving language skills by using cooperative learning. Keywords: speaking skills, cooperative learning, action research, vocational school